Pendampingan untuk Inisiasi Implementasi Konsep Green Hotel pada Entitas Bisnis Perhotelan - Pratama, Aryan Agus; Alpiansah, Restu; Yuliana, Ika; Jati, L. Jatmiko; Ramdani, Rizal (Insan Kreasi Media, 2024)
Rascals Hotel Kuta Lombok is an accommodation business entity located in the Mandalika Special Economic Zone, Central Lombok. Facing increasingly competitive business competition, this hotel provides excellent service with a beautiful environment and authentic traditional interior design. To maintain competitiveness, this hotel adopts technology but is limited to operational efficiency. The purpose of this activity is to build employee understanding and strengthen management initiatives to implement the green hotel concept. This activity is carried out through a series of socializations, digital service observations, and consultation discussions. The results of this activity show the high enthusiasm and initiative of hotel management to implement the green hotel concept. Employees have a basic understanding of the green hotel concept that strengthens resource assets. As a follow-up, it is necessary to create a strong management policy to strengthen long-term joint commitment and can improve operational efficiency and overall hotel competitiveness.